Peran Masyarakat dalam Pencapaian Target Sustainable Development Goals Desa Layak Air Bersih dan Sanitasi - Rina Susanti; Rifardi Rifardi; Yoskar Kadarisman (Mahesa Research Center, 2021)
The article aims to analyze the forms of role of community in the efforts to support the attainment of Sustainable Development Goals Village of clean water and sanitation. The study used perspective review over community participation by Keith Davis to take an approach over the problem. The data were collected through documentation and filling in the questionnaires by 158 households of Talontam village. The data were analyzed by using quantitative descriptive approach. The result of the study showed that to attain the sixth of Sustainable Development Goals village community who did not have access to clean water and sanitation participated in the forms of labor, idea, goods, and money that were executed in a form of saving money to build shallow borehole, hand-washing facilities, standard enclosed septic tanks and sanitations; building rainwater tanks; purchasing water filter; relocating septic tank; reusing used containers for hand washing; and participating in health counseling. The community group made efforts to maintain the sustainability of access to clean water and sanitation in the forms of conserving water and infrastructure maintenance, also preserve river area.